O007 The impact of physical activity on sleepiness among patients with obstructive sleep apnoea. A study from the Sydney Sleep Biobank. (9th November 2022) - Callum, J; Bin, Y; Sarkissian, N; Sutherland, K; Piper, A; Kairaitis, K; Wheatley, J; de Chazal, P; Yee, B; Cistulli, P
Abstract: BACKGROUND: Sleepiness is the most common symptom of obstructive sleep apnoea (OSA). Despite this the Epworth Sleepiness Score (ESS) has not been shown to predict OSA severity. We present the preliminary results of a cross-sectional analysis in OSA patients to examine the relationship between sleepiness and physical activity. METHODS: Participants aged >18, with an AHI >5, and no other sleep disorders were included. Sleepiness was defined as an Epworth Sleepiness Score (ESS) of >10. Physical activity was defined as quartiles of Metabolic Equivalent of Task (MET) minutes derived from the International Physical Activity Questionnaire (IPAQ). PROGRESS TO DATE: 593 participants were included (mean age 53.7, SD 14.4 years; 70.7% male; mean BMI 32.7, SD 8.5 kg/m2). 24.3% had ESS>=10 in the lowest quartile of physical activity, 28.2% in the 2nd quartile, 35.3% in the 3rd quartile and 30.2% in those with most activity. Controlling for OSA severity, gender, age or BMI, logistic regression showed increased sleepiness among participants in the 3rd quartile (3, 147–6, 426 MET-min/week) compared to the 1st quartile (<924 MET-min/week) with an odds ratio of 1.75 (95%CI 1.04–2.97). There was no interaction between OSA severity and physical activity. INTENDED IMPACT AND OUTCOME: Preliminary results suggest increased sleepiness among participants exerting 3, 147–6, 426 MET-min/week compared to <924 MET-min/week. Further analysis will consider frequency and type of physical activity (in addition to energy expenditure), additional confounding variables (e.g. sedating medication) and alternate measures of sleepiness (e.g. FOSQ-10).